‘To honour the treaty, we must first settle colonisation’ (Moana Jackson 2015): the long road from colonial devastation to balance, peace and harmony - Mutu, Margaret (Journal of the Royal Society of New Zealand, 2019)
Māori leaders in New Zealand continue the battle to end British colonisation. The aim is to restore the balance between Māori and the Crown guaranteed in the treaty that Māori and the British Crown agreed to in 1840 so that we can live in peace and harmony. Early European visitors subjected our ancestors to numerous atrocities. Relying on the Doctrine of Discovery, they illegitimately usurped our power and dispossessed us, leaving us in a state of poverty, deprivation and marginalisation. They fabricated myths to justify their criminal activities, set up an illegitimate parliament with unfettered powers, passed laws legalising their crimes and then covered it up with amnesia. They established the Waitangi Tribunal in 1975 to inquire into breaches of the treaty, not realising that it would dismantle the myths and look beneath the amnesia. Governments then instigated the ‘treaty claims settlement’ process to extinguish all Māori claims, remove Māori rights and entrench colonisation. Research undertaken has shown that Māori loathe this process and do not accept that settlements are full and final. Research on constitutional transformation has identified a possible solution. The first step towards that goal involves implementing the United Nations Declaration on the Rights of Indigenous Peoples.
Keywords: UNDRIP; colonisation; colonisation myths; constitutional transformation; crown; kāwanatanga; māori rights; oral history; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; treaty breaches; treaty settlements; waitangi tribunal

The treaty claims settlement process in New Zealand and its impact on Māori - Mutu, Margaret (2019)
This article considers research conducted on the impact of the Crown’s treaty claims settlement policy on Māori in New Zealand. It provides a brief background to the Treaty of Waitangi and the subsequent British colonisation process that relied on the Doctrine of Discovery in breach of the treaty. It outlines how colonisation dispossessed Māori of 95 percent of their lands and resources, usurped Māori power and authority and left them in a state of poverty, deprivation and marginalisation while procuring considerable wealth, prosperity and privilege for British settlers. The work of the Waitangi Tribunal, the commission of inquiry set up to investigate those breaches, is considered, as is the Crown’s reaction to the 1987 Lands case in developing its treaty claims settlement policy. The Crown unilaterally imposed the policy despite vehement opposition from Māori. Since 1992, it has legislated more than seventy ‘settlements’. The research shows that overall, the process has traumatised claimants, divided their communities, and returned on average less than one percent of their stolen lands. Proposals for constitutional transformation have drawn widespread support from Māori as a solution to British colonisation. United Nations treaty-monitoring bodies have recommended that the government discuss this with Māori
Keywords: colonisation; constitutional transformation; crown policy; law; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Behind the smoke and mirrors of the Treaty of Waitangi claims settlement process in New Zealand: no prospect for justice and reconciliation for Māori without constitutional transformation - Mutu, Margaret (Journal of Global Ethics, 2018)
Governments in New Zealand have legislated a large number of settlements extinguishing many hundreds of claims taken by Māori against the Crown for breaches of the country’s founding document, Te Tiriti o Waitangi. They portray settlements as a great success for Māori and the Crown. Māori disagree. Settlements are government-determined and imposed on Māori using a smoke and mirrors approach that masks successive governments’ true intentions: to claw back Māori legal rights; to extinguish all claims; and to maintain White control over Māori. In short, to uphold the Doctrine of Discovery in further breach of Te Tiriti o Waitangi. Māori claimants and negotiators report being enticed into the process by false promises only to become traumatised and disenchanted. Yet many take a pragmatic stance and sign settlements, making the best they can out of a bad deal that goes nowhere near compensating for their actual loss. They know that despite what legislation may say, the settlements are not full, not fair and not final and that, like all previous settlements, they will be revisited. They also know that unless fundamental changes are made to the constitutional makeup of the country, there is no prospect of justice and reconciliation for Māori.
Keywords: colonisation; constitutional transformation; doctrine of discovery; kāwanatanga; tiriti o waitangi/treaty of waitangi; trauma; treaty settlements; waitangi tribunal

Margaret Mutu: Why we need constitutional transformation - Mutu, Margaret (E-Tangata, 2022)
“The need for constitutional transformation has become quite clear in the Māori world over the last 12 or 13 years.” — Professor Margaret Mutu.
Keywords: constitutional transformation; he whakaputanga; mana motuhake; tiriti o waitangi/treaty of waitangi

Ngāti Kahu: portrait of a sovereign nation: history, traditions and Tiriti o Waitangi claims / Kia pūmau tonu te mana motuhake o ngā hapū o Ngāti Kahu - Mutu, Margaret; Pōpata, Lloyd; Williams, Te Kani; Herbert-Graves, Ānahera; Rēnata, Reremoana; Cooze, JudyAnn; Pineaha, Zarrah; Thomas, Tania; Kingi-Waiaua, Te Ikanui; Te Rūnanga-a-Iwi o Ngāti Kahu; Wackrow Williams and Davies Ltd (Huia Publishers, 2017)
"This book describes the iwi of Ngāti Kahu through the traditions and histories of each of the sixteen hapū, told by kuia and kaumātua and kept alive for future generations. These include histories of poverty, deprivation and marginalisation at the hands of the Crown, and loss of lands of the iwi. The book examines the range of techniques used by the Crown to justify its actions and the way these laid the groundwork for continuing injustices. The remedies needed to redress these injustices and achieve reconciliation of Ngāti Kahu and the Crown are set out. These include constitutional change to achieve the restoration of political, social and economic well-being to Ngāti Kahu, Crown relinquishment of all Ngāti Kahu lands to their rightful owners and payment of sufficient compensation to ensure no further Treaty of Waitangi claims. This history of Ngāti Kahu details the range of Crown actions against Ngāti Kahu to the current day, the effects of these actions on the people of Ngāti Kahu and the concerted and continuing efforts by Ngāti Kahu for remedies and reconciliation with the Crown"--Publisher information.
Keywords: colonisation; constitutional transformation; government relations; hapū; history; kāwanatanga; kōrero nehe; mana motuhake; ngāti kahu; noho-ā-iwi; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; treaty claims; tūpuna